Tissue Factor Pathway Inhibitor in Tetracycline-induced Pleuritis in Rabbits - Idell, Steven; Pendurthi, Usha; Pueblitz, Siegfried; Koenig, Kathleen; Williams, Todd; Rao, Vijay Mohan L. (Thrombosis and Haemostasis, 1998)
Pleural fibrin deposition that promotes loculation and fibrosis after pleural injury is initiated by tissue factor (TF). In this study, we sought to determine if tissue factor pathway inhibitor (TFPI), an inhibitor of the TF-factor VIIa complex, was likewise expressed in tetracycline (TCN)-induced pleural injury and, if so, whether TFPI was locally elaborated. Pleural fluid TFPI activity approximated that of plasma by 24 h and doubled by 3 days after intrapleural TCN. By contrast, pleural fluid coagulation factors VII and V remained below plasma concentrations at these intervals. Immunohistochemical studies demonstrated TF, TFPI and fibrin localized in pleural and subpleural tissues and within intrapleural adhesions. TFPI activity and mRNA were also elaborated by rabbit pleural mesothelial cells and lung fibroblasts. TFPI is locally expressed and pleural fluid TFPI exceeds plasma levels during TCN-induced pleural injury. Resident cells as well as extravasation likely contribute to intrapleural TFPI. TFPI expression temporally and anatomically approximates that of TF and may limit TF-induced fibrin deposition in evolving TCN-induced pleuritis.